Dynamics of perceived threat and media exposure during the COVID-19 pandemic - Talia Morstead; Nancy L. Sin; Anita DeLongis (SSM - Mental Health)
The COVID-19 pandemic media landscape was characterized by an unrelenting stream of disease-related information that varied in tone, factual accuracy, and degree of ascribed certainty. Given the increasing centrality and integration of media technology in daily life, examining how media exposure contributed to individuals' experiences coping with the threat of COVID-19 is crucial. In this study, we used longitudinal data from 3189 primarily North American participants, collected monthly from June 2020 through January 2021 to examine reciprocal associations among media exposure, COVID-19 thought frequency, and perceived threat of COVID-19 at the within-person level of analysis. Drawing on a transactional model of stress and coping to frame our investigation, we hypothesized that increases from one's typical level of media exposure, COVID-19 thought frequency, or perceived threat of COVID-19 in a given month would predict increases in these variables in the subsequent month. Apart from the effect of media exposure on perceived threat of COVID-19, results from random intercept cross-lagged panel models supported our hypotheses, revealing cyclical effects at the within-person level. Additionally, between-person associations indicated that those who scored highly on any of the three study variables, also tended to score highly on the others. Effects at the within-person level suggest a potential vicious cycle of media exposure, COVID-19 thought frequency and perceived threat of COVID-19 at the height of the pandemic. The findings aid in identifying targets for intervention that can be leveraged to mitigate adverse physical and mental health impacts in the context of future pandemics and other global crises.